Development of Waja Based CNGDI Passenger Vehicle Rear Platform Component - Sahari, Barkawi; Ahmad, Mohd. Fauzy; Chelliah, V. (2006)
The development of a compressed natural gas vehicle (CNGV) for passenger car is of interest nationally and worldwide, particularly with the rise in petrol prices. The main components of a CNGV are the body, engine and transmission and fuel storage. For the vehicle body development, many aspects need to be considered. These are the on board fuel storage locations, crashworthiness, strength and vibration characteristics. For petrol vehicle, the shape of the fuel storage can be designed to fit the space available underneath the vehicle body structure. However, for CNGV, the shape of the gas storage is always cylindrical. Hence, the vehicle body structure is to be designed to fit the cylindrical storage tanks underneath the platform as well as the passengers above it. In addition, the ergonomic passenger compartment and crashworthiness need also to be considered. This paper presents the analysis of a rear platform of Waja body to fit the CNG tanks. The result for the crash characteristics of the CNG rear platform is presented. It is compared with that of the corresponding petrol platform and discussed. The effect of the CNG rear platform on the natural frequency and stiffness of the vehicle body is also presented and discussed.